Offshore financial system - blessing or a curse - Mathavious, Robert (IMF WashingtonUS, 2000)
Focuses on the practical implications for offshore financial centres arising out of the increased scrutiny and the avalanche of initiatives targeting Offshore Financial Centres (OFCs) emanating from the developed world and the impact this new world order will have on how the offshore fiinancial system operates in the 21st century.